Business strategy influence of facebook online apparel retailers on consumers' attitude (focus on School of Business Management female postgraduate students) - Nurul Nadhrah, Hasni (2016)
The advancement of technology nowadays has led to the changes of human lifestyle by providing opportunities for them to access internet anywhere they want using the mobile gadgets. This situation allows the users to purchase goods and services through online store, especially from the online stores on social media network sites like the apparel stores on Facebook. This situation creates opportunities to individual and organization to start doing online business. However, not all of the online retailers manage to survive in the virtual market for a long period of time due to poor business strategy plan. Therefore, the purpose of this study was to investigate the influence of the business strategy of online apparel retailers on Facebook using the marketing mix model towards the consumers‘ attitude among School of Business Management (SBM) female postgraduate students while making purchasing decision. A survey data was collected from a total number of 197 SBM, Universiti Utara Malaysia female postgraduate students as respondents, and the data was analyzed by using the Statistical Package Social Science (SPSS) 22nd version software. Based on the analysis findings, it was found that the product strategy, distribution strategy and promotion strategy has a positive significant relationship with the female consumers‘ attitude, while the price strategy was found not to be significant to female consumers‘ attitude. Promotion strategy showed the strongest positive relationship with the female consumers‘ attitude compared to the other independent variables. Recommendations and suggestions that can be used by future researchers and apparel online retailers have been suggested at the end of the study.